2022
DOI: 10.21203/rs.3.rs-1439273/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRISPR/Cas9-Mediated Knockdown Of BRCA1/2 Restores Response To Olaparib In Pancreatic Cancer Cell Lines

Abstract: Background: Pancreatic cancer is one of the most aggressive diseases with a very poor outcome. Olaparib, a PARP inhibitor, as maintenance therapy showed benefits in patients with metastatic pancreatic adenocarcinoma bearing germline BRCA1/2 mutations and that did not undergo progression during at least 16 weeks of a prior platinum-based chemotherapy regimen. However, germline BRCA mutation has been described in only 4 to 7% of patients with pancreatic adenocarcinoma. Methods: A CRISPR/Cas9-mediated system was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…They discovered several mesenchymal-specific regulators, such as Egfr and Mfge8, that were responsible for inhibiting immune cell function [470]. The application of CRISPR/Cas9 technology to introduce targeted BRCA1/2 mutations enables the reinstatement of olaparib responsiveness in pancreatic cancer cells [471]. Apart from potential challenges and limitations of CRISPR/ Cas9 such as off-target toxicity, Cas9-related immunogenicity, and off-target mutations, these studies highlight the useful application of this genome editing tool in the context of pancreatic cancer immunotherapy.…”
Section: Crispr/cas9 and Pancreatic Cancer Immunotherapymentioning
confidence: 99%
“…They discovered several mesenchymal-specific regulators, such as Egfr and Mfge8, that were responsible for inhibiting immune cell function [470]. The application of CRISPR/Cas9 technology to introduce targeted BRCA1/2 mutations enables the reinstatement of olaparib responsiveness in pancreatic cancer cells [471]. Apart from potential challenges and limitations of CRISPR/ Cas9 such as off-target toxicity, Cas9-related immunogenicity, and off-target mutations, these studies highlight the useful application of this genome editing tool in the context of pancreatic cancer immunotherapy.…”
Section: Crispr/cas9 and Pancreatic Cancer Immunotherapymentioning
confidence: 99%
“…CTCs, originating from primary tumors or metastatic sites, can enter and circulate within the bloodstream [4] . Containing the complete genomic information of the primary lesion, CTCs hold significant value for disease detection [5] . Earlier studies, through transcriptomic sequencing, have identified significant differences in the expression of long non-coding RNAs (lncRNAs) between radiotherapy-sensitive and radiotherapy-tolerant CRC patients, with a notable upregulation of HOXA-AS2 in the latter.…”
Section: Introductionmentioning
confidence: 99%